An examination of substance use status and personality traits in university students - Onan, Nevin; Kaplan, Hilal; Yalçın, Büşra; Erbaş, Sümeyye; Yıldırım, Deniz; Ünsal Barlas, Gül; Karaca, Semra; Öz, Yüksel Can (Journal of Dependence, 2016)
Objective: The aim of this study is to examine the relationship between university students’ substance use conditions and personality traits.Method: This descriptive and crosssectional study sampling was constituted by 745 students who agreed to participate in the study, between January-March 2014 at a state university. The data were collected using Information Form, Eysenck Personality Inventory-short form and were evaluated by descriptive statistical analysis and Mann-Whitney U test.Results: The average age of students was 21.22 ± 20. 51.8% of the students were male. 88.5% of the parents of students are married and live together. 40.7% of the students are using substances. It was determined that 32.2% of them were smoking, 23.6% of them use alcohol and 0.4% of them use opioid substances. When the students’ substance use status and personality characteristics were compared, a statistically significant difference was found between extraversion (Z=3.63, p=.000) and psychoticism property (Z=8.21, p=.000) and substance use conditions. According to these findings, the mean scores of extraversion and psychoticism subscales are higher in the students used substance than the students who not used substance.Conclusions: According to the results of this study; students’ personality traits are associated with substance abuse conditions. In line with these findings; it was concluded that risk groups in substance abuse should be identified and training and consultancy services as well as mental health services among university students should be structured in protective and preventive actions.
Keywords: Student; personality traits; alcohol and substance use